1991
DOI: 10.1089/hyb.1991.10.575
|View full text |Cite
|
Sign up to set email alerts
|

Monoclonal Antibody for Avian Thymic Hormone

Abstract: Avian thymic hormone (ATH), a parvalbumin with immunomodulating properties, was used as antigen for development of a hybridoma cell line. Hybridoma screening by enzyme-linked immunosorbent assay (ELISA) led to the culture, purification, and characterization of an hybridoma, designated 4A6, which secretes IgG1 that is specific for ATH. The monoclonal antibody (MAb) was characterized by techniques involving indirect competitive and non-competitive ELISA, Western Blot analysis, and immunohistological staining. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
10
0

Year Published

1993
1993
2003
2003

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 6 publications
1
10
0
Order By: Relevance
“…In post-hatched chickens, these cells contain numerous electron-light and electron-dense cytoplasmic vesicles (Frazier 1973;Kendall 1980), whose number was related to progressive cell maturation during ontogeny (Sugimoto et al 1977). The observation that cortical RECs establish close relationships with thymocytes (Kendall 1980(Kendall , 1991, and contain hormones such as the avian thymic hormone/parvalbumin (Hall et al 1991;Kiraly and Cello 1993) that could promote thymocyte differentiation (Barger et al 1991;Hall et al 1991;Murthy and Ragland 1992), highlighted the functional correlation between these cell types.…”
Section: Cortical Reticular Epithelial Cellsmentioning
confidence: 99%
“…In post-hatched chickens, these cells contain numerous electron-light and electron-dense cytoplasmic vesicles (Frazier 1973;Kendall 1980), whose number was related to progressive cell maturation during ontogeny (Sugimoto et al 1977). The observation that cortical RECs establish close relationships with thymocytes (Kendall 1980(Kendall , 1991, and contain hormones such as the avian thymic hormone/parvalbumin (Hall et al 1991;Kiraly and Cello 1993) that could promote thymocyte differentiation (Barger et al 1991;Hall et al 1991;Murthy and Ragland 1992), highlighted the functional correlation between these cell types.…”
Section: Cortical Reticular Epithelial Cellsmentioning
confidence: 99%
“…For more than a decade Ragland and his coworkers (Barger et al 1977;Murthy and Ragland 1984) have studied a protein isolated from chicken thymus, called Avian Thymic Hormone (ATH), and have found that it promotes the development of T-lymphocytes (Murthy et al 1984a, b). It has been reported that the nucleic acid sequence of ATH (Brewer et al 1989;Henzl 1990, 1991a, b;Henzl et al 1991 ;Serda and Henzl 1991) is nearly the same as that of parvalbumin (PV) from chicken, turtle and amphibian muscle (Strehler et al 1977;Heizmann and Strehler 1979;Hall et al 1991). Since PV is found intracellularly in muscles (P6ch~re et al 1973;Celio and Heizmann 1982) and brain (Celio and Correspondence to: M.R.…”
Section: Introductionmentioning
confidence: 99%
“…Human tissue was employed in the present study mainly because (1) the information obtained from animal studies cannot be always extrapolated to humans and (2) some developmentally transient structures of the human cortex may be structurally different or even absent in animals Sidman and Rakic, 1982;Spreafico et al, 1999). For example, the expression of some calcium binding proteins in humans has been found to be different from those in rodents and chickens (Hall et al, 1991;Heizmann et al, 1982;Huber et al, 1990;Murthy et al, 1984). In the present study, three antibodies against S100A4, S100A5, and S100A13 have been used to immunohistochemically localize the proteins on the brain sections.…”
Section: Introductionmentioning
confidence: 99%